DNA methylation inhibitors adverse reaction characteristic analysis: an analysis based on the European spontaneous adverse event reporting system - Zhang, Xia; Liu, Yuyu; Hou, Qingwang; Guo, Yongxin; He, Youfu (Frontiers in Pharmacology, 2025)
IntroductionDNA methylation inhibitors have been approved for the prevention of Acute Myeloid Leukemia (AML), and their safety profile is not fully characterized. This study was aimed at evaluating the adverse drug reactions (ADRs) of DNA methylation inhibitors by analyzing the individual case safety reports (ICSRs) collected in the EudraVigilance (EV) database.Materials and methodsThe EV database managed by the European Medicines Agency was adopted. The standardized medical terminology set MedDRA was utilized. The ICSRs data of DNA methylation inhibitors for the treatment of acute myeloid leukemia originated from the EV database (2005–2024). A descriptive exploration of the combined data from EV was undertaken to assess the age, gender of patients, severity and outcome of ADR, event year, geographical origin and the qualification of the reporting source. A comprehensive assessment was made for severe ADR cases. By means of the Reporting Odds Ratio (ROR) and 95% Confidence Interval (CI), a non-proportional analysis was made for MedDRA® SOC in DNA methylation inhibitors. Statistical analysis was executed with SPSS version 23.0, and p < 0.05 was regarded as statistically significant.ResultThe study reveals that reports related to AZACITIDINE increased from 2005 to 2023, with a slight decline in 2024, while those for DECITABINE have been on the rise since 2007. ICSRs were associated with a majority of males and individuals aged 65–85. Healthcare professionals frequently reported ICSRs related to DNA methylation inhibitors. A significant portion of these ICSRs were serious and completely resolved. The most common ADRs were identified, and certain ADRs had a higher reporting probability with AZACITIDINE (e.g., Febrile neutropenia, Anamia, etc.) and others with DECITABINE (e.g., Myelosuppression, Thrombocytopenia, etc.).ConclusionThe analysis regarding ADRs of DNA methylation inhibitors was consistent with the literature information disclosed. AZACITIDINE and DECITABINE each have ADRs with a high probability of being reported. Although the study has the advantage of using the database, it is limited by the spontaneous reporting system. Future improvements are needed to accurately evaluate the safety of the drugs.